Shinto, a short history - Teeuwen, Mark 1966- (RoutledgeCurzon, 2003)
Shinto - A Short History provides an introductory outline of the historical development of Shinto from the ancient period of Japanese history until the present day. Shinto does not offer a readily identifiable set of teachings, rituals or beliefs; individual shrines and kami deities have led their own lives, not within the confines of a narrowly defined Shinto, but rather as participants in a religious field that included Buddhist, Taoist, Confucian and folk elements. Thus, this book approaches Shinto as a series of historical 'religious systems' rather than attempting to identify.